THE SCHOOL AND THE ELEMENTARY EDUCATION I, IN FACE OF LEARNING DIFFICULTIES: ASPECTS FOR A DISCUSSION AGENDA ON THE (DE)MEDICALIZATION OF EDUCATION AND THE SUCCESS OF SCHOOLS - Castro, Rosane Michelli de [UNESP]; Oliveira Reis, Karina Cassia [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
In this article, we explore aspects about the role of the school and the teaching of schoolchildren, given the learning difficulties presented during Elementary School I (1st to 5th year) and that concern the necessary distancing from diagnoses that have led to the medicalization of Education. We focus on theorizations that emphasize the importance of intentional teaching, of action-reflection-action of the teacher. We present what is characteristic of the school team, the pedagogical interventions, in different places of the school space to meet the learning needs presented by the children, especially those with difficulties in carrying out the activities. For that, we prioritize presenting results of pedagogical interventions through the tour class. The target audience for our intervention was elementary schools I (1st to 5th grade). The tour class, inspired by Freinet's thinking, allowed us to offer other possibilities for the children to recognize and systematize, with the help of the most experienced partner, the proposed activities, especially those that favor the cognitive exercise of reading and of writing by children considered to have learning difficulties. Indistinctly, all children demonstrated their appropriations, showing success in all activities. Thus, we consider that educators and other subjects in the school community, especially family members, should not mistakenly treat learning difficulties as psychological or psychiatric disorders, resorting to diagnoses that lead to the medicalization of schoolchildren, therefore, Education, and distance the school and its teachers from what is the essence of the teaching action that is didactic-pedagogical.
Keywords: Education; Elementary School I; (De)medicalization of Education; Essentiality of teaching action; Learning difficulties